Self-employment and field of education understood from current entrepreneurship research. Issue 3 (14th September 2015) - Silke Tegtmeier, Prof. Jay Mitra, Dr.; Berggren, Caroline; Olofsson, Anders
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to look at how results from a large-scale study can be understood in the context of contemporary gender and entrepreneurship research. Design/methodology/approach – This study is inspired by a mixed methods methodology. To gain a qualitative understanding of the general patterns in a large-scale study, research results in articles from the International Journal of Gender and Entrepreneurship (IJGE) were used. To make such a heterogeneous research field as appears in IJGE comparable, a model was created that helped us to focus our attention when reading the articles. The core of each article was identified. Findings – The categorisation of the articles in IJGE resulted in three perspectives: liberal, functional and structural. The liberal and functional perspectives improved our understanding only partially because these perspectives usually focused on a certain aspect in the society. The structural perspective more readily lent itself for interpretation of our large-scale results. Research limitations/implications – The dissonance between our perspective and the perspective of others has been a challenge; it has been a delicate task. Originality/value – This could be a way to improve communication of research not only within a perspective, but also between perspectives. It is important that scholarly journals provide the possibility to express different perspectives on, as in this example, gender and entrepreneurship.